Women in the Paintings of Johannes Vermeer and (Edward Hopper) A Comparative Research - Mohammad Salh Rostam Zadeh (Zanco Journal of Humanity Sciences)
Women have always been one of the most important subjects of works of visual arts, especially painting. And this shows the importance and status of women in different societies. Jean Vermeer, a Dutch artist of the Baroque era, and Edward Hopper, an American artist of contemporary origin, are those painters whose women's faces are very evident as an important element in their works. This research compares the image of women in the works of these two artists in order to measure the position and identity of women in two different historical periods and between two different geographies. For this purpose, I have used the comparative method and library sources in this research. The achievements tell us that women's faces in the works of art of each period show the status of women and the social, economic, cultural and artistic status of that period.